Six decades of changes in the riparian corridor of a Mediterranean river: a synthetic analysis based on historical data sources. Issue 4 (4th October 2012) - Garófano‐Gómez, V.; Martínez‐Capel, F.; Bertoldi, W.; Gurnell, A.; Estornell, J.; Segura‐Beltrán, F.; Blanckaert, Koen; Garcia, Xavier‐François; Steiger, Johannes; Uijttewaal, Wim
ABSTRACT Riparian corridors in semi‐arid Mediterranean environments are ecosystems of high biodiversity and complexity. However, they are threatened because of high levels of human intervention. River damming and related flow manipulation is considered as one of the most prominent human impacts on riparian corridors. This study combines historical time series information on river flows and their human manipulation, historical aerial images depicting changes in riparian land cover and ground observations of the species – age composition and morphology of the riparian corridor of a Mediterranean river (the Mijares River, Eastern Spain) over the last 60 years. In this sense, we explored how to integrate information from a wide variety of data sources, and we extracted a variety of indices and undertook analyses that identified and summarized spatio‐temporal changes in riparian structure and in the driving flow processes. Results revealed an increase in the cover and density of woody vegetation and a decrease in bare sediment areas (essential for recruitment of riparian pioneer species), with a synchronous reduction in the complexity of the riparian corridor of the middle reaches of the Mijares River. These vegetation changes have accompanied a decrease in the magnitude and variability of river flows over the last six decades, with higher severity since dam closure. This study illustrates the effectiveness of combining disparate historical data sources and the effectiveness of processing these sources to extract informative metrics that can improve the understanding and management of riparian systems. Copyright © 2012 John Wiley & Sons, Ltd.